Niche Contractions in Declining Species: Mechanisms and Consequences. (May 2017) - Scheele, Ben C.; Foster, Claire N.; Banks, Sam C.; Lindenmayer, David B.
Abstract : A fundamental aim of conservation biology is to understand how species respond to threatening processes, with much research effort focused on identifying threats and quantifying spatial and temporal patterns of species decline. Here, we argue that threats often reduce the realized niche breadth of declining species because environmental, biotic, and evolutionary processes reduce or amplify threats, or because a species' capacity to tolerate threats varies across niche space. Our 'niche reduction hypothesis' provides a new lens for understanding why species decline in some locations and not others. This perspective can improve management of declining species by identifying where to focus resources and which interventions are most likely to be effective in a given environment. Trends: Existing approaches to characterizing species declines focus on geographic patterns of declines, or the distribution of threats, with too little attention paid to the processes involved We propose the niche reduction hypothesis: a new lens that focuses on the processes leading to species declines The realized niche of species can be substantially reduced by threats because environmental, biotic, and evolutionary processes reduce or amplify threat impacts, or because a species' capacity to tolerate threat impacts varies across niche space. The niche reduction hypothesis can provide new insights into why species decline in some environments and not others and help determine where to focus conservation resources